Osteotomy models – the current status on pain scoring and management in small rodents. (December 2016) - Lang, Annemarie; Schulz, Anja; Ellinghaus, Agnes; Schmidt-Bleek, Katharina
Fracture healing is a complex regeneration process which produces new bone tissue without scar formation. However, fracture healing disorders occur in approximately 10% of human patients and cause severe pain and reduced quality of life. Recently, the development of more standardized, sophisticated and commercially available osteosynthesis techniques reflecting clinical approaches has increased the use of small rodents such as rats and mice in bone healing research dramatically. Nevertheless, there is no standard for pain assessment, especially in these species, and consequently limited information regarding the welfare aspects of osteotomy models. Moreover, the selection of analgesics is restricted for osteotomy models since non-steroidal anti-inflammatory drugs (NSAIDs) are known to affect the initial, inflammatory phase of bone healing. Therefore, opioids such as buprenorphine and tramadol are often used. However, dosage data in the literature are varied. Within this review, we clarify the background of osteotomy models, explain the current status and challenges of animal welfare assessment, and provide an example score sheet including model specific parameters. Furthermore, we summarize current refinement options and present a brief outlook on further 3R research.